Cholesterol incorporation into bovine oocytes prior to vitrification favors recovery of GM1 level at the plasma membrane - Buschiazzo, Jorgelina (2013)
Methyl-β-cyclodextrin (MβCD) saturated with cholesterol or alone was used to modulate plasma membrane cholesterol level of metaphase II bovine oocytes. Membrane biophysical state of oocytes and cumulus cells was evaluated at decreasing temperatures and changes in the localization of the raft marker GM1 were analyzed in Cryotop vitrified oocytes. After 2 hours of incubation with 15 mM MβCD saturated with cholesterol, fluorescence intensity of BODIPY-cholesterol at the plasma membrane increased. Oocytes that were incubated with MβCD alone showed no differences in membrane fluorescence intensity but evidenced changes in the distribution of cytoplasmic lipid droplets. Laurdan generalized polarization revealed that membrane fluidity of oocytes is lower than that of cumulus cells at temperatures closer to the physiological but this relation is inverted when temperature decreases below 20°C. GM1 loss caused by vitrification was restored when cholesterol was incorporated into oocytes before vitrification and removed after warming, thus indicating that membrane raft integrity can be preserved by cholesterol modulation.